THE ROLE OF RELIGIOUS VALUES IN THE FORMATION OF CRIMINAL LAW IN INDONESIA - Gunawan Widjaja (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2025)
This research examines the role of religious values in the process of criminal law formation in Indonesia. Referring to Pancasila as the foundation of the state, the value of Belief in One God emphasises the importance of religious aspects in national legislation. The moral values of the various religions practised by Indonesians, particularly Islam, Christianity and Hinduism, have influenced a number of provisions in the Kitab Undang-Undang Hukum Pidana (KUHP). Examples of these provisions include prohibitions against adultery and alcohol consumption, which resonate with the moral teachings of the dominant religions. However, the application of religious values in criminal law also faces challenges related to religious pluralism. Therefore, the legislative process should take into account inclusive dialogue and consultation with various religious groups to ensure that the resulting laws are not discriminatory and still respect the diversity of beliefs, in order to maintain social harmony in Indonesia.